2006
DOI: 10.1002/jae.896
|View full text |Cite
|
Sign up to set email alerts
|

The welfare effects of restricted hospital choice in the US medical care market

Abstract: SUMMARYManaged care health insurers in the USA restrict their enrollees' choice of hospitals to within specific networks. This paper considers the implications of these restrictions. A three-step econometric model is used to predict consumer preferences over health plans conditional on the hospitals they offer. The results indicate that consumers place a positive and significant weight on their expected utility from the hospital network when choosing plans. A welfare analysis, assuming fixed prices, implies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 30 publications
(14 reference statements)
6
76
0
Order By: Relevance
“…Bene…ciaries value the size or breadth of the physician network because they must commit to a provider network at the time of purchasing insurance and a broader network reduces the probability of needing more expensive out-of-network services in the event of an illness. 21 The referral indicates the restrictiveness of the network. In addition to including the referral variable, the physician network size and the referral variable are interacted to capture the e¤ect of the 1 9 www.meps.ahr.gov 2 0 The information about each plan is available to the public through the medicare options compare website (http://www.medicare.gov/MPPF).…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bene…ciaries value the size or breadth of the physician network because they must commit to a provider network at the time of purchasing insurance and a broader network reduces the probability of needing more expensive out-of-network services in the event of an illness. 21 The referral indicates the restrictiveness of the network. In addition to including the referral variable, the physician network size and the referral variable are interacted to capture the e¤ect of the 1 9 www.meps.ahr.gov 2 0 The information about each plan is available to the public through the medicare options compare website (http://www.medicare.gov/MPPF).…”
Section: Data and Variablesmentioning
confidence: 99%
“…For instance, numerous studies have found that consumers tend not to travel far hospital services (e.g. Gaynor and Vogt (2003) and Ho (2006)). While the above arguments suggest that bene…ts in other geographic markets are valid instruments, it is important to note that if the bene…ts in other geographic markets are correlated with demand shocks, then the reported estimates are likely to be biased.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…We rst contribute to the literature on patient choice and modeling patient demand. In particular, we complement existing work that has estimated discrete choice models of hospital choice [Beckert et al, 2012;Kessler and McClellan, 2000;Ho, 2006], by showing that for non-emergency care these types of models could be enhanced or extended by including an outside option of no procedure.…”
mentioning
confidence: 86%
“…Existing work on hospital choice has focused on which hospital patients choose, taking the set of patients as given [Beckert et al, 2012;Ho, 2006;Kessler and McClellan, 2000] 1 . However, for most nonemergency health conditions, hospital care can be delayed or avoided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation